The Effect of Mangats Application in Improving Social Studies Learning Outcomes at SMP Negeri 11 Malang - Setyawan Triaditama; Pratiwi, Ilmia; Azizah, Nuril; Fauzan, Zumrotus Sholihah; Muhammad Asyroful Mujib (International Journal of Geography, Social, and Multicultural Education, 2025)
This study aims to determine the effect of the application of Mangats (Modul Semangat Nasionalisme) on improving student learning outcomes in the subject of Social Studies at SMP Negeri 11 Malang. The background of this research is social studies learning that is considered less interesting by students because it is theoretical and less relevant to everyday life, so that the learning provided by teachers tends to be limited to textbooks. The lack of innovation in the learning process makes students less interested in learning the material. This results in many students experiencing a decrease in interest in learning and low learning outcomes, especially in material about the lives of Indonesian people during colonialism and imperialism. This study used a quantitative approach with a quasi-experimental design through pretest and posttest measurements on two groups, namely the experimental group that used the Mangats application and the control group that did not use it. Data were collected through observation, questionnaires, and tests. The data were analyzed using Paired Sample T-test to see the difference in pretest and posttest results in both groups. The results of the analysis showed that the use of the Mangats application significantly improved student learning outcomes, with the average value of the posttest being much higher than the pretest. This shows that the Mangats application is effective in increasing students' interest and understanding in Social Studies subjects at SMP Negeri 11 Malang